A magyarországi dolgozó korú népesség halandósága: Makroelemzés időben és térben - Mária Lackó (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– The study analyses the development of Hungarian mortality rates of working age population and its explanatory factors. The analysis uses two approaches: first an international cross-sectional comparison for the year 2011, and then a time series examination with the help of a "health production function", based on Hungarian data for the period 1972-2009. In both approaches we investigate the mortality rates of males and females separately. In the international cross sectional comparison of 46 countries of Europe and CIS countries turns out that the huge differences in mortality rates are to a great extent determined by the long term past of the political and economic systems in the preceding decades. According to the "state socialist syndrome of mortality", in the post socialist economies mortality rates have been much higher than in long term capitalist countries, especially for men. Cross country differences in male mortality are influenced by a series of factors: latitude of the countries, GDP per capita in the countries, relative prices and consumption of unhealthy products (alcohol, especially spirit, and tobacco), the share of the informal or hidden economy in total production, level of education of the population, and the share of health expenditure in GDP. For females factors related to lifestyle explain differences in mortality rates in a less pronounced way than for males. [...]
Keywords: I12; 330; mortality rates; cross country comparison; health production function; Hungary